Advertisement call and colour in life of Allobates crombiei (Morales) “2000” [2002] (Anura: Aromobatidae) from the type Locality (Cachoeira do Espelho), Xingu River, Brazil - Lima, Albertina P.; Erdtmann, Luciana K.; Amézquita, Adolfo (Zootaxa, 2012)
Allobates crombiei was described by Morales, “2000” [2002] based on specimens collected by Ronald I. Crombie from Cachoeira do Espelho, on the right bank of the Xingu River, Pará State, Brazil. The original description was short and did not include the call or colour in life. Rodrigues & Caramaschi (2004) suggested that the taxonomic status of this species need be clarified. We are confident that the species collected and recorded by us is Allobates crombiei (Morales) “2000” [2002] because this is the only species of Allobates found calling in forest near Cachoeira do Espelho, and the character diagnosis in preserved specimens is similar, except that, based on preserved specimens, Morales (2002) considered the ventrolateral and the oblique lateral stripes to be absent. This may be because they are imperceptible in preserved specimens. However, unlike recent authors, Morales (2002) also considered the oblique lateral stripe to be absent in Allobates brunneus, Allobates gasconi and Allobates ornatus, in which he illustrated diffuse spots.